Effect of a pre-exercise energy supplement on the acute hormonal response to resistance exercise - Hoffman, J. R.; Ratamess, N. A.; Ross, R.; Shanklin, M.; Kang, J.; Faigenbaum, A. D. (The Journal of Strength and Conditioning Research, 2008)
The effect of a pre-exercise energy sport drink on the acute hormonal response to resistance exercise was examined in eight experienced resistance trained men. Subjects were randomly provided either a placebo (P: maltodextrin) or the supplement (S: combination of branched chain amino acids, creatine, taurine, caffeine, and glucuronolactone). Subjects performed 6 sets of no more than 10 repetitions of the squat exercise at 75% of their 1 repetition maximum (1RM) with 2 minutes of rest between sets. Blood draws occurred at baseline pre-exercise, immediately post- (IP), 15 minutes post- (15P), and 30-minutes post (30P) exercise for measurement of serum growth hormone, total and free testosterone, cortisol, and insulin concentrations. Although significant differences were seen only at set 5, the total number of repetitions and training volume tended (p = 0.08) to be higher with S compared to P. Serum growth hormone and insulin concentrations were significantly higher at 15P and IP, respectively, in S compared to P. Results suggest that a pre-exercise energy S consumed 10 minutes before resistance exercise can enhance acute exercise performance by increasing the number of repetitions performed and the total volume of exercise. The enhanced exercise performance resulted in a significantly greater increase in both growth hormone and insulin concentrations, indicating an augmented anabolic hormone response to this pre-exercise S.